A 2danalytical model of the channel potential and threshold voltage of double-gate (dg) mosfets with vertical gaussian doping profile - Tiwari P.K.; Kumar S.; Mittal S.; Srivastava V.; Pandey U.; Jit S. (My University, 2025)
The paper presents a 2D analytical model for the potential function and threshold voltage of symmetric Double- Gate (DG) MOSFETs with vertical Gaussian doping profile in the channel. © 2009 IEEE.